Characterization of film yeast isolated from fermented bamboo shoots - Maneesri, Jaruwan; Masniyom, Payap (Asia-Pacific Journal of Science and Technology, 2017)
The characterization of film yeasts (Saccharomyces cerevisiae J1, Candida krusei J2 and C. krusei J3) isolated from fermented bamboo shoots were studied. The morphological change of C. krusei J2 and C. krusei J3 showed the cell extension about 6% on the nitrogen limitation in liquid synthetic low-ammonia dextrose medium (SLAD), while S. cerevisiae J1 exposed the highest of the cell extension about 21% within 24 h on solid yeast extract peptone dextrose medium (YPD) containing 0.5 %(v/v) isoamyl alcohol. The viable cells of film yeasts were investigated at various temperatures. These film yeasts can grow at 0, 40 and 50 oC but they were not survived at high temperature than 60 oC. S. cerevisiae J1 can tolerate to 18% (w/v) glucose and the gas production was shown higher than 12 ml in liquid YPD. But C. krusei J2 and C. krusei J3 produced low a gas production. S. cerevisiae J1 was 0.10 g/ml of the glycerol production in liquid YPD medium containing 2.5% (w/v) NaCl, whereas C. krusei J3 and C. krusei J2 were only 0.077 and 0.058 g/ml, respectively. Killer activity of these film yeasts to five sensitive reference yeast strains (C. tropicalis TISTR 5045, Hansenula anomala TISTR 5113, S. cerevisiae TISTR 5020, S. cerevisiae TISTR 5055 and Torulopsis glabrata TISTR 5241) was examined on medium with 0.003%(w/v) methylene blue. All film yeasts were killer yeasts to five sensitive reference yeast strains.